Impact of human, structural and relational capital on educational needs of SMEs in Croatia - Švarc, Jadranka (Array, 2013)
Competitiveness of companies in knowledge economy is determined by their intangible assets dominated by intellectual capital and their propensity towards education and training. The purpose of research is to analyse the relationship between the three components of intellectual capital (human, structural and relational) and educational needs using the example of Croatia. The relationships with other companies’ characteristics such as business performance, size, type of industry, etc. are also analysed. The analysis revealed that companies with higher level of intellectual capital are more aware of the benefits and of the need for entrepreneurial education, show better business performance while employees’ satisfaction, motivation, risk taking and innovativeness is higher. In order to find out which types and modes of entrepreneurial education companies need, we have examined their preferences towards five aspects of education and training. They revealed that the most needed knowledge is about financial aspects of business and “soft” skills like leadership and management principles. Entrepreneurs prefer problem solving lectures to standard lectures and need consultations related to taxes and legal issues. They feel a need to cooperate with other entrepreneurs and need consultancy how to deal with investors and local community.